CD Contributors' Notes. (Leonardo Music Journal, 2005)
The article reviews several music releases including "Kana," composed and performed by Tomomi Adachi, "O som que circula nas veias/The Sound That Circulates in the Veins," written and performed by Américo Rodrigues, "Cyborg Opera," composed and performed by Christian Bök, "Vielleicht," performed by Axel Kühn, Oliver Hahn, Klaus Sperber, Thomas Eberhardt and Michael Lentz and "OOA," composed by Vincent Barras and Jacques Demierre.